Organisational sustainability transition: Utilisation of the Backcasting theory to increase sustainability in the organisation CPAC - Andersson, David; Eriksson, Jakob (My University, 2020)
CPAC is a company located in Mölndal, Sweden, that develops electrical control systems for Volvo Group. They strive to always be one step ahead in development and now they want to confirm that they are sustainable and perform activities that actually contributes to a positive change. This thesis aims to expand CPACs awareness of their environmental footprint, to create an action plan for how to increase internal motivation and striveto develop products that contributes to a sustainable future. This study uses the back-casting methodology to reduce the risk of getting caught in current problems the organisation is facing today. By creating a framework of principles based on the company’s values and aspirations, it is possible to trace those goals backwards to identify a strategic path to achieve those goals. This methodology is backed up by the self-determination theory that is used to understand what motivates people as individuals and as a group to strengthen the results that will come from this project. Together with this methodology different strategies to gather information has been used. Dialogues were performed with employees from different segments and levels within the organisation to gather information about the current situation. Different workshop setups were organised to determine the wanted future state of the organisation and to identify the gaps and challenges in between those two states. The final result is an action plan for how to reach the desired future state and how to implement sustainability throughout the organisation. Though the final result of implementation will not be visible in this project due to the time it will take to perform, it will give a recommendation of how to raise the awareness and implement sustainability with a natural approach.
Keywords: sustainability, development, sustainable development, organisation; organisational management, CPAC